External rapid convenience monitoring of measles-rubella campaign 2017 and lessons learned: Study from a hilly district of North India - Devender Kumar; Vijay Kumar Barwal; Amit Sachdeva; Anmol Gupta (Wolters Kluwer Medknow Publications, 2020)
Introduction: The most recent vaccine incorporated in the Universal Immunization Program of India is measles-rubella vaccine, introduced as a catch-up campaign to eliminate measles and control rubella by the year 2020. The success of any immunization campaign lies on its meticulous planning for areas such as trainings, cold chain management, advocacy, and social mobilizations. Rapid convenience monitoring (RCM) was done in nine health blocks of a hilly district of Himachal Pradesh, pertaining to various campaign activities, for determining vaccine coverage and side effects. Material and Methods: Standardized formats developed by the World Health Organization for RCM of the quality of activity at session sites which included information regarding vaccinating teams, immunization sites, logistics used, cold chain and aseptic condition management, waste disposal, and record maintenance were used. School and house-to-house visits were conducted randomly to check the indelible ink mark/vaccination cards to find out any missed child. Results: A total of 107 immunization sessions were observed for compliance. We assessed 1182 children between the age group of 9 months and 15 years for determining vaccine coverage during the measles-rubella campaign in September-October 2017. Compliance to various aspects of the campaign was found very good, exceeding 90% in almost all the domains. The total vaccination coverage was 98.1%. Schools and health-care providers were the major source of information for this campaign. No severe adverse events following immunization were reported during the survey. Conclusion: Activity compliance and vaccination coverage were found high. Adequate supply of indelible ink pens and functional hub cutters needs to be ensured. There should be revision of incentives to team members with increased involvement of accredited social health activist workers in such campaigns.